A prospective observational study on the stress levels at the time of embryo transfer and pregnancy testing following in vitro fertilisation treatment: a comparison between women with different treatment outcomes. (25th September 2018) - Cheung, CWC; Saravelos, SH; Chan, TYA; Sahota, DS; Wang, CC; Chung, PW; Li, TC
Abstract : Objective: To ascertain whether stress biomarkers and psychological indices of stress may predict both conception and miscarriage rates in women undergoing in vitro fertilisation/intracytoplasmic sperm injection (IVF/ICSI). Design: Prospective observational study. Setting: A university‐affiliated tertiary hospital. Population: Infertile women who were undergoing fresh or frozen IVF/ICSI cycles. Methods: Women were recruited to (1) complete validated psychological questionnaires (visual analogue scale of stress, state–trait anxiety inventory, perceived stress scale, fertility problem inventory, Beck depression inventory, and general health questionnaire), at the time of embryo transfer (ET) and pregnancy testing (PT), and (2) provide saliva samples for α‐amylase (sAA) measurement before and after ET and at PT. Main outcome measures: Women were grouped according to subsequent reproductive outcome; scores/levels of all tests were then compared between groups at each time‐point. Results: In all, 197 women completed the study, of which 92 conceived and 28 miscarried. The level of psychological stress, as measured by questionnaires, was highest at the time of PT, whereas the level of biological stress as measured by sAA level (IU/l) post‐ET (1.8 × 10 5  ± 1.5 × 10 5 ) was significantly ( P  < 0.001) higher than pre‐ET (1.2 × 10 5  ± 1.0 × 10 5 ) and at PT (1.0 × 10 5  ± 1.1 × 10 5 ). However, there was no difference in psychological scoring and in sAA levels between women who did or did not conceive and who had miscarried or had an ongoing pregnancy. Conclusions: The level of sAA is highest following ET, whereas psychological stress is highest at PT. However, neither stress level appeared to be of prognostic value in predicting conception or miscarriage. Tweetable abstract: Stress level fluctuated at different time‐points, but it did not predict conception or miscarriage. Tweetable abstract: Stress level fluctuated at different time‐points, but it did not predict conception or miscarriage.